Preserving traditional mosques in Madinah - Omer, Spahic (IslamiCity, 2019)
Preserving relevant traditional mosques was another trend with respect to the evolution of the contemporary mosque architecture in Madinah. The trend was inspired by the way the Prophet’s Mosque successfully integrated tradition into its own avant-garde outlook and form. Peaceful coexistence between old and new, tradition and modernity, in the Prophet’s Mosque’s complex configuration and function was a benchmark against which major architectural tendencies and styles in Madinah are normally measured. The idea of maintaining certain traditional mosques does not contradict discourses on architectural corrective measures in the city, whereby a number of mosques with which some untoward beliefs and practices had been associated, were either destroyed or abandoned and increasingly rendered inaccessible. This is so because those relevant traditional mosques were originally meant to be the places of prayer (worship) and functioned as such for long periods. They were then turned into full-fledged mosques that served the needs of local communities. Some, since their inceptions, were yet envisioned to be fully functional mosques. Their functions were meant to encompass several other substantial public educational and social aspects too.